Peningkatan Pemahaman Matakuliah Jaringan Komputer Dasar Menggunakan Simulator Jaringan Cisco Packet Tracer - Martanto; Saeful Anwar (Jurnal ICT: Information Communication & Technology, 2020)
Students studying at STMIK IKMI Cirebon have diverse school backgrounds, so not all students have an adequate basis for computer science, this can be seen in the final examination results of the basic computer network subject for the previous generation of Informatics Management study program, the KHS score got better because it is helped by the value of the assignment and the value of the certification. To simplify the understanding, students can use the Cisco packet tracer network simulator. The effectiveness of the Cisco packet tracer network simulator can be analyzed using the Quasiexperiments method. This analysis method is the method used in this study by using the Time Series Design as a collaboration in classroom action research. There are three main stages in this method, namely: 1) pretest 4 times, 2) special treatment using the Cisco Packet Tracer network simulator for 6 meetings, 3) Pretest 4 times. The results of this study get the Asymp value. Sig. for the ANOVA test of 0,000. The ANOVA value of 0.000 indicates that the PreTest and PostTest scores have a difference where the PostTest results have been proven to be better, so it can be concluded that learning activities using the Cisco Packet Tracer Network Simulator can improve student understanding